2022
DOI: 10.1177/11786361221093278
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Retailed Poultry: Analysis of Antibiotic Resistance in Escherichia coli From Raw Chicken and Poultry Fecal Matter From Selected Farms and Retail Outlets in Accra, Ghana

Abstract: Purpose: To assess the safety of retailed poultry using the prevalence of antibiotic resistance in Escherichia coli ( E. coli), a dominant intestinal microflora. Methods: Two medium-scale farms and 8 well-known retail outlets within the La-Nkwantanang Madina municipality in Accra were purposively selected for sampling from January to March 2020. We randomly sampled raw chicken (n = 25) and poultry fecal matter (n = 50). All samples were immediately transported on ice to the laboratory for analysis within 12 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 87 Additionally, our findings are consistent with those reported in other studies. 14 , 53 , 60 , 85 , 94 The resistance of E. coli to ampicillin may indicate the misuse of penicillins in the poultry sector. Additionally, studies in humans have also reported high resistance of E. coli to ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“… 87 Additionally, our findings are consistent with those reported in other studies. 14 , 53 , 60 , 85 , 94 The resistance of E. coli to ampicillin may indicate the misuse of penicillins in the poultry sector. Additionally, studies in humans have also reported high resistance of E. coli to ampicillin.…”
Section: Discussionmentioning
confidence: 99%
“…The un-due usage of antimicrobials is also rendering meat/ eggs for human consumption as well as transfer the resistance to humans (Dube and Mbanga, 2018). Principles of Hazard Analysis and Critical Control Point (HACCP) make sure about consumption of chicken meat under the strict rule of surveillance and adherence to avoid the antimicrobial resistant contaminated strains through food chain (Mensah et al, 2022). Raw chicken meat is ideal substrate for contamination of infected strain due to poor hygienic condition, lack of knowledge about antimicrobial destruction while consuming the meat (Odwar et al, 2014) Therefore, in this cross sectional study, we investigated the phenotypic and genotypic basis of antimicrobial resistance among E. coli isolates from meat producing commercial chickens from different commercial farms located in Faisalabad-Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their inherent nature of dwelling human and animal food resources, rats are frequently seen in the household and farm environment especially poultry farms in Bangladesh. Recently, colistin resistant and MDR E. coli has been reported from fecal samples and poultry farm environments in Bangladesh and other part of the world [10,14,20] indicating a high chance of rats being exposed to such critical pathogens. And because of shared habitat, rats might be involved in the transmission of AMR including colistin resistant E. coli to human and livestock especially to poultry farms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, colistin resistant and MDR E . coli has been reported from fecal samples and poultry farm environments in Bangladesh and other part of the world [ 10 , 14 , 20 ] indicating a high chance of rats being exposed to such critical pathogens. And because of shared habitat, rats might be involved in the transmission of AMR including colistin resistant E .…”
Section: Introductionmentioning
confidence: 99%